Les pénitenciers bordelais pour enfants. 1838-1870 - Allemandou, Bernard (PrimaLun@, 2021)
Author of two monographs on the care of abandoned children in Bordeaux published by the MSHA, Bernard Allemandou, child psychiatrist, focuses here on the fate of poor children who commit crimes. The Saint-Jean penitentiary, created in 1837 for minor boys, and the Sainte-Philomène penitentiary the following year for girls, were born of the flaw in the incarceration system practised at the time, where children were not separated from adult prisoners. Based on documents kept in the municipal archives of Bordeaux and the departmental archives of the Gironde, the author describes the functioning of these two institutions, which operated until 1870. Given the failure of the State to create special establishments, private initiative was encouraged, leaving this task to the clergy, who, as a "work of charity", intended to give instruction to minors where "they would learn to know, to serve, to fear and above all, to love God". From the penitentiaries to the agricultural colonies, Bernard Allemandou thus paints a portrait of a Bordeaux society torn between the necessary and saving Christian charity of the time and the fear of these delinquent children who had to live in uncomfortable buildings with uncertain financing, with a summary education and incomplete food.